No wealth but life : welfare economics and the welfare state in Britain, 1880 - 1945 - Backhouse, Roger E. , 1951-; Nishizawa, Tamotsu , 1950- (Cambridge University Press, 2010)
"This book re-examines early-twentieth-century British welfare economics in the context of the emergence of the welfare state. There are fresh views of the well-known Cambridge School of Sidgwick, Marshall, Pigou, and Keynes, by Peter Groenewegen, Steven G. Medema, and Martin Daunton. This is placed against a less well-known Oxford approach to welfare: Yuichi Shionoya explores its foundations in the idealist philosophy of T. H. Green; Roger E. Backhouse considers the work of its leading exponent, J. A. Hobson; and Tamotsu Nishizawa discusses the spread of this approach in Britain. Finally, the book covers welfare economics in the policy arena: Maria Cristina Marcuzzo and Atsushi Komine discuss Keynes and Beveridge, and Richard Toye points to the possible influence of H. G. Wells on Churchill and Lloyd George. A substantial introduction frames the discussion, and a postscript relates these ideas to the work of Robbins and subsequent developments in welfare economics"--Provided by publisher